2000
DOI: 10.4049/jimmunol.165.10.5987
|View full text |Cite
|
Sign up to set email alerts
|

Progression from Acute to Chronic Disease in a Murine Parent-into-F1 Model of Graft-Versus-Host Disease

Abstract: The parent-into-immunocompetent-F1 model of graft-vs-host disease (GVHD) induces immune dysregulation, resulting in acute or chronic GVHD. The disease outcome is thought to be determined by the number of parental anti-F1 CTL precursor cells present in the inoculum. Injection of C57BL/6 (B6) splenocytes into (B6 × DBA/2)F1 (B6D2F1) mice (acute model) leads to extensive parental cell engraftment and early death, whereas injection of DBA/2 cells (chronic model) results in little parental cell engraftment and a lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 28 publications
0
52
0
1
Order By: Relevance
“…Although GVHD induced in CB6F 1 mice is generally similar to that in B6D2F 1 , as described above, strain-dependent differences have been identified. BALB/c-into-CB6F 1 resulted in chronic GVHD that was comparable to that of DBA/2-into-B6D2F 1 (26). The aGVHD resulting from C57BL/6-into-CB6F 1 , characterized by donor cell expansion and antihost CTL activity, was similar to that in C57BL/6-into-B6D2F 1 during the first 3 wk following transfer (26).…”
Section: B and T Lymphocyte Attenuator (Btla)mentioning
confidence: 66%
See 1 more Smart Citation
“…Although GVHD induced in CB6F 1 mice is generally similar to that in B6D2F 1 , as described above, strain-dependent differences have been identified. BALB/c-into-CB6F 1 resulted in chronic GVHD that was comparable to that of DBA/2-into-B6D2F 1 (26). The aGVHD resulting from C57BL/6-into-CB6F 1 , characterized by donor cell expansion and antihost CTL activity, was similar to that in C57BL/6-into-B6D2F 1 during the first 3 wk following transfer (26).…”
Section: B and T Lymphocyte Attenuator (Btla)mentioning
confidence: 66%
“…In this model, transfer of C57BL/6 donor cells into C57BL/6 ϫ BALB/c F 1 (CB6F 1 ; H-2 b/d ) yields aGVHD, whereas BALB/c donor cells produce chronic GVHD (26). Although GVHD induced in CB6F 1 mice is generally similar to that in B6D2F 1 , as described above, strain-dependent differences have been identified.…”
Section: B and T Lymphocyte Attenuator (Btla)mentioning
confidence: 98%
“…High frequency of alloreactive lymphocytes, the engraftment of parental anti-F1 CTL and the production of type-1 cytokines favor the development of acute GvHD, while chronic GvHD is characterized by a low frequency of alloreactive lymphocytes, the absence of host CD8 engraftment and the production of type-2 cytokines [26][27][28][29][30]. In response to allogeneic stimulation in vitro, LEW and BN alloreactive CD45RC high CD4 T cells exhibited different profiles of cytokine production and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, highdose C57BL/6 splenocytes induce acute epithelial GvHD that is lethal over several months. 14 In contrast, high-dose C57BL/6 LN cells induces a BMGvHD, which is rapidly lethal; [15][16][17] BMGvHD is also seen if recipients are irradiated, in which case lower quantities of C57BL/6 T cells are required. Here, we found that challenge of B6DBA2F1 with C57BL/6 splenocytes gave rise to two distinct outcome patterns.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Earlier studies in the C57BL/6-B6DBA2F1 model showed that high-dose C57BL/6 splenocytes induce acute epithelial-tissue GvHD that is lethal over several months. 14 In contrast, high-dose C57BL/6 lymph node (LN) cells induces a BM failure type of GvHD (BMGvHD), which is rapidly lethal; [15][16][17] BMGvHD is also seen if recipients are irradiated, in which case lower quantities of C57BL/6 T cells are required. The characteristics of parent-in-F1 GvHD is equally known to vary between strain combinations, and to depend on strainspecific alloreactive T-cell-precursor frequency.…”
Section: Introductionmentioning
confidence: 99%